Cover, Content, and Editorial Note from PengabdianMu: J Pengabdian Masyarakat Vol. 3 No. 2 September 2018 - Chief Editor of PengabdianMu: J Pengabdian Masyarakat (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2018)
Assalamu’alaikum Wr. Wb. Alhamdulillahirabbil ‘alamin. The latest edition of PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat Vol. 3 No. 2 September 2018 has been published. This edition contains 8 articles consisting of several article with the topics of community services in the multidisciplinary areas. Editorial boards are fully aware that there is still room for improvement in this edition, hence with all humility willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. We hope that all parties, especially the contributors of the articles, could participate in the success of the publication in the next edition in March 2019. Wassalamu’alaikum Wr. Wb.